Space use of invertebrates in terrestrial habitats: Phylogenetic, functional and environmental drivers of interspecific variations - Gwenaëlle Auger; Julien Pottier; Jérôme Mathieu; Franck Jabot (Global Ecology and Biogeography, 2024)
Aim We present the first global database of movement patterns of terrestrial invertebrates, focusing on active dispersal and foraging movements. We depict interspecific variations in movement distances among invertebrates and assess potential drivers of these variations. We finally contrast our results with those of previous vertebrate studies. Location Worldwide. Methods We conducted a meta‐analysis using 176 studies. They provided 411 movement estimates: 175 foraging movement estimates for 101 species, 51 families and 19 orders, and 236 dispersal estimates for 131 species, 53 families and 16 orders. These estimates were complemented by several organism functional traits: body mass, diet, locomotion mode and by environmental variables of the study sites: temperature and NDVI. We computed allometric relationships between movement distances and body mass both globally and separately for each taxonomic order with sufficient data. We tested the relative influence of the co‐variables on movement distances through model selection. Results We reveal a general positive allometric relationship between movement distance and body mass that holds across most taxonomic orders. We evidence a strong phylogenetic signal in movement distances that translates in variable allometries of movement distances with body mass across taxonomic orders. We further find that interspecific variations of movement distances are primarily correlated with functional differences rather than environmental conditions. Locomotion mode is the most important explanatory variable of both dispersal and foraging distances, with larger distances among flying individuals followed by walking and crawling ones for a given body mass. Surprisingly, trophic guild has a low predictive power of invertebrate movement distances as opposed to vertebrates, with unclear differences between invertebrate carnivores, herbivores and decomposers. Main Conclusions Our study provides general allometric equations for terrestrial movement distances of invertebrates. It further reveals important functional drivers of their interspecific variation in space use with a dominant role of their evolutionary history.

Multiple glacial refugia and contemporary dispersal shape the genetic structure of an endemic amphibian from the Pyrenees - Federica Lucati; Manon Poignet; Alexandre Miró; Audrey Trochet; Fabien Aubret; Laurent Barthe; Romain Bertrand; Teresa Buchaca; Olivier Calvez; Jenny Caner; Elodie Darnet; Mathieu Denoël; et al. (Molecular Ecology, 2020)
Historical factors (colonization scenarios, demographic oscillations) and contemporary processes (population connectivity, current population size) largely contribute to shaping species’ present‐day genetic diversity and structure. In this study, we use a combination of mitochondrial and nuclear DNA markers to understand the role of Quaternary climatic oscillations and present‐day gene flow dynamics in determining the genetic diversity and structure of the newt Calotriton asper (Al. Dugès, 1852), endemic to the Pyrenees. Mitochondrial DNA did not show a clear phylogeographic pattern and presented low levels of variation. In contrast, microsatellites revealed five major genetic lineages with admixture patterns at their boundaries. Approximate Bayesian computation analyses and linear models indicated that the five lineages likely underwent separate evolutionary histories and can be tracked back to distinct glacial refugia. Lineage differentiation started around the Last Glacial Maximum at three focal areas (western, central and eastern Pyrenees) and extended through the end of the Last Glacial Period in the central Pyrenees, where it led to the formation of two more lineages. Our data revealed no evidence of recent dispersal between lineages, whereas borders likely represent zones of secondary contact following expansion from multiple refugia. Finally, we did not find genetic evidence of sex‐biased dispersal. This work highlights the importance of integrating past evolutionary processes and present‐day gene flow and dispersal dynamics, together with multilocus approaches, to gain insights into what shaped the current genetic attributes of amphibians living in montane habitats.

Identification of two new trichome-specific promoters of Nicotiana tabacum - Mathieu Pottier; Raphaëlle Laterre; Astrid Van Wessem; Aldana M. Ramirez; Xavier Herman; Marc Boutry; Charles Hachez (Planta, 2020)